Factors Influencing The Duration Of Illness to Mortality In Confirmed COVID-19 Patients Admitted to Hospitals Across Riau Province - Rachmawati, Fitri; Adisasmita, Asri. C. (Indonesian Health Journal (IHJ), 2023)
This study aims to look at the factors associated with the length of illness to death in COVID-19 patients being treated in hospitals throughout Riau Province. Researchers used secondary data sourced from data from the Online Hospital at the Riau Provincial Health Office. The overall cumulative survival probability for dying was 6.2%, with an overall median survival time of 20 days (IQR: 17-22). The lowest median survival time is the initial saturation value variable, which is 4 days (IQR: 2-5), the use of a respirator is 5 days (IQR: 3-6), and ICU care is 8 days (95% CI: 8-9) ). The final results of multivariate analysis showed that old age had a 1.7 times risk of experiencing death HR 1.747 (95% CI: 1.386-2.202), a low initial saturation value had a 1.6 times risk of experiencing death HR 1.627 (95% CI: 1.155-2.292), care units in the ICU have a 1.9 times risk of dying with HR 1.911 (95% CI: 1.439-2.538) and patients who use respirators have a 1.4 times risk of dying with HR values 1.463 (95% CI: 1.051-2.037). Improvement and readiness of referral health facilities in Riau Province is something that deserves attention as a preventive effort in facing the possibility of the next emerging disease.